2008
DOI: 10.1063/1.3013441
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interlayer trapping and detrapping mechanisms on the electrical characterization of hafnium oxide/silicon nitride stacks on silicon

Abstract: Al/ HfO 2 / SiN x :H/ n-Si metal-insulator-semiconductor capacitors have been studied by electrical characterization. Films of silicon nitride were directly grown on n-type silicon substrates by electron cyclotron resonance assisted chemical vapor deposition. Silicon nitride thickness was varied from 3 to 6.6 nm. Afterwards, 12 nm thick hafnium oxide films were deposited by the highpressure sputtering approach. Interface quality was determined by using current-voltage, capacitance-voltage, deep-level transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
2
16
0
1
Order By: Relevance
“…faces can be charged or discharged, distorting the DLTS signal and overestimating the D it value 14,15. Here, ␤ PF is the Poole-Frenkel parameter, ⌬E A is the activation energy related to the PF emission, N DIGS is the DIGS density value, and B is the barrier height in the Fowler-Nordheim tunneling.…”
mentioning
confidence: 99%
“…faces can be charged or discharged, distorting the DLTS signal and overestimating the D it value 14,15. Here, ␤ PF is the Poole-Frenkel parameter, ⌬E A is the activation energy related to the PF emission, N DIGS is the DIGS density value, and B is the barrier height in the Fowler-Nordheim tunneling.…”
mentioning
confidence: 99%
“…On the other hand, the D it values of nanolaminated and Al 2 O 3 based structures should not appreciably differ because of the first high-k material in direct contact on silicon is Al 2 O 3 in both cases, i.e., the same Al 2 O 3 /Si interface is fabricated. However, we have observed that for stacked insulators, traps existing at different dielectric interfaces can be charged or discharged, distorting DLTS signal and overestimating the D it value [10][11]. This effect can be also identified from the conductance transient technique results leading to DIGS densities (N DIGS ) shown in Table I.…”
Section: Resultsmentioning
confidence: 75%
“…On the other hand, although aluminium oxide permittivity (10) is lower than hafnium oxide one (25), its gap is larger and has a barrier height higher with respect to silicon substrate and specifically, the use of Al 2 O 3 as a blocking layer in stacked structures induces a large voltage drop across the tunneling layer and enhances the operation speed of memory devices [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…We can see how DIGS states are preferentially located at energies in the range 50-100 meV under the silicon conduction band. Although DIGS densities are not too much high, these values may be higher than in unannealed samples (16).…”
Section: Resultsmentioning
confidence: 98%